2020
DOI: 10.1007/s10930-020-09933-w
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Crystallized Structures of the SARS-CoV-2

Abstract: Many research teams all over the world focus their research on the SARS-CoV-2, the new coronavirus that causes the so-called COVID-19 disease. Most of the studies identify the main protease or 3C-like protease (M pro /3CL pro ) as a valid target for large-spectrum inhibitors. Also, the interaction of the human receptor angiotensin-converting enzyme 2 (ACE2) with the viral surface glycoprotein (S) is studied in depth. Structural studies tried to identify the residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 162 publications
(138 reference statements)
0
35
0
Order By: Relevance
“…Importance of the GxxxG motif was reported on the SARS-CoV-2 proteins 46 . Mimicry and molecular mimicry are among the methods of the evolutionary arms race [47][48][49] and mimicry was proposed as a mechanism to explain multi-organ damage in COVID-19 50 .…”
Section: #17 Molecular Mimicry Evolution Unique Motif and Beta-lactamasementioning
confidence: 99%
“…Importance of the GxxxG motif was reported on the SARS-CoV-2 proteins 46 . Mimicry and molecular mimicry are among the methods of the evolutionary arms race [47][48][49] and mimicry was proposed as a mechanism to explain multi-organ damage in COVID-19 50 .…”
Section: #17 Molecular Mimicry Evolution Unique Motif and Beta-lactamasementioning
confidence: 99%
“…Importantly, a stabilising mutation at NSP 3 may suggest a mechanism which differentiates COVID-19 from SARS [ 58 , 59 ]. NSP 3 has a major role in suppressing the host’s innate immunity, and is associated with the inflammation produced in severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…NSP 3 has a major role in suppressing the host’s innate immunity, and is associated with the inflammation produced in severe COVID-19. Furthermore, the increased infectivity of SARS-CoV-2, in contrast to SARS-CoV-1, may be related to a destabilising mutation at NSP 2 [ 58 , 59 ]. Interestingly, the PL pro of SARS-CoV-1 preferentially cleaves ubiquitin over ISG15 [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few months, several small molecules have been described as possible inhibitors of different molecular targets for SARS-CoV-2 [ 36 ]. However, it is important to note that many of these studies are still in the initial in silico analyses, which only provide a preliminary theoretical view on the ligand–protein interactions and hence requiring experimental validation of the molecular targets [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the molecular targets of SARS-CoV-2, main protease or 3-chymotrypsin-like protease (M pro /3CL pro /nsp5) [ 37 ], papain-like protease (PL pro /nsp3) [ 38 ], RNA-dependent RNA polymerase (RdRp/nsp12) [ 39 ], and helicase/NTPase (nsp13) [ 40 ] could be cited, which are highly conserved and essential to the viral cycle [ 36 , 41–45 ], as illustrated in Figure 2 . Since the main viral protease is extensively studied for the design of new drug candidates to treat coronaviruses diseases, and most of the studies identified this enzyme as a valid target for broad spectrum inhibitors, we will next focus on the discussion of this macromolecule in more details [ 33 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%